2020
DOI: 10.1038/s41598-020-63280-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin is required in vivo for the stability of bacterial translocon and optimal membrane protein translocation and insertion

Abstract: translocation of preproteins across the Escherichia coli inner membrane requires anionic lipids by virtue of their negative head-group charge either in vivo or in situ. However, available results do not differentiate between the roles of monoanionic phosphatidylglycerol and dianionic cardiolipin (CL) in this essential membrane-related process. To define in vivo the molecular steps affected by the absence of CL in protein translocation and insertion, we analyzed translocon activity, SecYEG stability and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 78 publications
2
27
0
Order By: Relevance
“…S5 ). This data indicates that CL modulates the activity of the mitochondrial rhomboid protease PARL by enhancing its overall structural stability through protein–lipid interactions, similar to other mitochondrial proteins ( 32 , 33 ). Therefore, CL was included in all subsequent protein preparations of detergent-solubilized PARL at the last purification step.…”
Section: Resultsmentioning
confidence: 60%
“…S5 ). This data indicates that CL modulates the activity of the mitochondrial rhomboid protease PARL by enhancing its overall structural stability through protein–lipid interactions, similar to other mitochondrial proteins ( 32 , 33 ). Therefore, CL was included in all subsequent protein preparations of detergent-solubilized PARL at the last purification step.…”
Section: Resultsmentioning
confidence: 60%
“…In S. mutans, SecA and Sortase also co-localize to a discrete microdomain similar to the S. pyogenes ExPortal , and it has been reported that S. mutans virulence factors such as P1 (aka SpaP, PAc, AgI/II), glycosyltransferase, and fructosyltransferase utilize this microdomain for secretion particularly during growth in biofilms (Huang et al, 2008). Bacterial co-translational and post-translational protein transport pathways converge at the membrane-localized SecYEG translocon (Ryabichko et al, 2020). While SecA is generally associated with post-translational protein transport, it can also associate with ribosome nascent chain complexes to support co-translational transport (Huber et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…SecA has also been reported to oligomerize and interact with a dimeric SecYEG complex (Gold et al, 2010). The stability of SecYEG dimers and SecA oligomers is severely compromised following the engineered absence of cardiolipin in the inner membrane of Escherichia coli, thereby impeding translocation and insertion of several known protein substrates (Ryabichko et al, 2020). Thus, the relative proportions of cardiolipin in the S. mutans EMVs compared to corresponding CMs (higher in WT EMVs, lower in srtA and sfp EMVs) would impact the efficiency of secretion, or membrane protein insertion, of substrates that depend on dimerization of SecYEG and/or oligomerization of SecA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CL at a molar ratio of 50:1 caused a 100-fold increase of PINK1 cleavage, while only a 4-fold increase at a molar ratio of 100:1 (Fig 1D). This suggests that CL may modulate the activity of the mitochondrial rhomboid protease PARL by enhancing its overall structural stability through protein-lipid interactions, similar to other mitochondrial proteins (Ghosh et al, 2020;Ryabichko et al, 2020). It is also worth mentioning that CL is known to induce curvature in membranes (McMahon & Boucrot, 2015), which could alter the activity of PARL protease.…”
Section: Lipids Enhance Parl Activitymentioning
confidence: 91%